2023
DOI: 10.18632/aging.204656
|View full text |Cite
|
Sign up to set email alerts
|

TYRO3 promotes tumorigenesis and drug resistance in colorectal cancer by enhancing the epithelial-mesenchymal transition process

Abstract: Colorectal cancer (CRC) is a leading cause of cancer mortality worldwide. Although considerable advances in CRC treatment have been achieved, effective treatment improvement has hit a bottleneck. This study demonstrated that TYRO3 expression was aberrantly increased in CRC tissues with prognosis association. The prediction model of prognosis for CRC patients was constructed based on TYRO3 expression. The model suggested that the TYRO3 level is crucial to the final prediction results. We observed that knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…High amounts of these reactive molecules activate lipid peroxidation, leading to the death of the tumor cell [ 51 ]. A study by Shao et al [ 52 ] revealed that TYRO3 expression was found to be increased in colorectal cancer cells, and blocking this receptor improved the efficacy of 5-fluorouracil treatment. The findings in this study further suggest that inhibiting TYRO3 may be another promising method to reduce cancer resistance to PD-1 therapy.…”
Section: Reviewmentioning
confidence: 99%
“…High amounts of these reactive molecules activate lipid peroxidation, leading to the death of the tumor cell [ 51 ]. A study by Shao et al [ 52 ] revealed that TYRO3 expression was found to be increased in colorectal cancer cells, and blocking this receptor improved the efficacy of 5-fluorouracil treatment. The findings in this study further suggest that inhibiting TYRO3 may be another promising method to reduce cancer resistance to PD-1 therapy.…”
Section: Reviewmentioning
confidence: 99%